Unidirectional Spin Hall Magnetoresistance as a Tool for Probing the Interfacial Spin Polarization of Co2MnSi - Lidig, C.; Cramer, J.; Weisshoff, L.; Thomas, T. R.; Kessler, T.; Klaeui, M.; Jourdan, Martin (Physical Review Applied, 2019)
Many Heusler compounds are predicted to be ferromagnetic half metals in the bulk, which makes them promising compounds for spintronics. However, for devices the transport spin polarization at specific interfaces requires optimization. We show that investigations of the unidirectional magnetoresistance provide an alternative approach to access this quantity. Based on a Wheatstone-bridge design we probe the unidirectional magnetoresistance of Co2MnSi/(Ag, Cu, or Cr)(0.5 nm)/Pt (or Ta) multilayers and separate the spin-dependent unidirectional spin Hall magnetoresistance from other contributions. We demonstrate that by the insertion of a thin epitaxial Ag layer the spin-dependent contribution is doubled corresponding to a significant increase of the transport spin polarization, which is discussed in the framework of highly spin-polarized interface states.
CRIS-Team Scopus Importer:2023-03-27